Meta-Analysis Study: Application of Technology Enhanced Learning Model on Student Learning Outcomes - Putra, Rifan Gusnadi; Koto, Rahmat Desman; Wagino , Wagino; Maksum, Hasan; Saputra, Hendra Dani; Fernandez, Donny (EduLine: Journal of Education and Learning Innovation, 2025)
This article discusses the application of the Technology Enhanced Learning (TEL) learning model and its impact on student learning outcomes. This study aims to evaluate the effectiveness of TEL in improving students' skills and understanding in vocational subjects. The method used was a quantitative research with an experimental design, involving two groups of students: one group using the TEL model and a control group applying traditional learning methods. Data was obtained through learning outcome tests, questionnaires, and observations. The results of the analysis showed that students who participated in learning with TEL had a significant improvement in learning outcomes compared to the control group. These findings indicate that the application of the TEL model can improve student motivation, engagement, and understanding, as well as provide recommendations for further integration of technology in the learning process. Thus, this research highlights the importance of innovation in learning methods to prepare students to face challenges in an increasingly digital world of work.